Weather based forecasting model for incidence of downy mildew of pearl millet in Coimbatore - and M. RAMIAH, A. KRISHNAVENI, P. RAJA* (Indian Phytopathology, 2008)
Analysis of simple correlation and multiple correlation and regression between the incidence of downy mildew in pearl millet and weather factors like rainfall (avg.55.3mm) and minimum temperature (avg.21.45Â° C) showed positive correlation to the development of downy mildew incidence one week before diseases incidence compared to other weather parameters. The prevalence of rainfall (avg. 45.30mm) and minimum air temperature (avg.20.832C) during the vegetative phase (30 days after sowing) suggested maximum incidence of downy mildew at Coimbatore. One unit increase of independent variables like temperature (min.) and rainfall increases downy mildew incidence to 0.41 and 0.48 per cent and 9.14 and 0.32 per cent at 30DAS respectively.